Treatment of chromium solutions in a 15 dm3 pilot bioreactor - Quintelas, C. (2008)
Chromium is a heavy metal with large industrial applications such as in textile dying, chemicals and pigments production, wood preservation, tanning activity and electroplating for surface treatment. The treatment of wastewater containing this metal with biological methods is strongly recommended, especially when in the form of Cr (VI) due its high toxicity. The biosorption system consists of a bacterial biofilm supported on granular activated carbon (GAC), placed in contact with the polluted solutions. The bacterium used for the formation of the biofilm was Arthrobacter viscosus. Two concentrations of chromium were used: 10 mg/l and 100 mg/l, with a flow rate of 25 mg/l. The data obtained in a pilot-scale reactor showed an average removal percentage of 99.9%, during the first 30 days, for the initial concentration of 10 mg/l and average removal percentage of 72%, for the same period and for the initial concentration of 100 mg/l. Uptake values of 11.35 mg/gGAC and 14.55 mg/gGAC were obtained, respectively, for the initial concentration of 10 and 100 mg/l. The presence of functional groups on the cell wall surface of the biomass that may interact with the metal ion was confirmed by FTIR. The results obtained are very promising and encourage the utilization of this biofilm in environmental applications.